Processing and properties of low cost macroporous alumina ceramics with tailored porosity and pore size fabricated using rice husk and sucrose - Mohanta K.; Kumar A.; Parkash O.; Kumar D. (My University, 2025)
The present study demonstrates a cost effective way to fabricate porous ceramics with tailored microstructures using rice husk (RH) of various range of particle sizes as a pore former and sucrose as a binder as well as a pore former. Sample microstructures reveal randomly oriented elongated coarse pores and fine pores (avg. size 4 μm) created due to burnout of RH and sucrose, respectively. Porous alumina ceramics with 20-66. vol% porosity and 50-516 μm avg. pore size (length), having isolated and/or interconnected pores, were fabricated using this process. Mechanical properties of the porous samples were determined as a function of porosity and pore microstructure. The obtained porous ceramics exhibited flexural strength of 207.6-22.3. MPa, compressive strength of 180-9.18. MPa, elastic modulus of 250-18. GPa and hardness of 149-18 HRD. Suggested application area includes thermal, filtration, gas purging etc. © 2014 Elsevier Ltd.